Chemiluminescent determination of leukocyte alkaline phosphatase: An advantageous alternative to the cytochemical assay - Kanegae, Marilia P. P.; Ximenes, Valdecir Farias [UNESP]; Falcao, Roberto P.; Colturato, Virgilio A. R.; de Mattos, Ederson R.; Brunetti, Iguatemy Lourenço [UNESP]; Marcos da Fonseca, Luiz (Wiley-Blackwell, 2007)
The determination of leukocyte alkaline phosphatasd (LAP) is used as an aid to diagnose many diseases in the laboratory. For example, it can be used to distinguish chronic myeloid leukemia (CML) from other myeloproliferative disorders (particularly myelofibrosis and polycythemia) and leukemoid reactions (LR). Traditionally, this test is performed with the use of subjective cytochemical assays that assign a score to the level of LAP. Here we present a nonsubjective, quantitative, sensitive, and inexpensive chemiluminescent technique that determines LAP based on the commercial reagent Immulite (R) (AMPPD). To validate this methodology, intact leukocytes obtained from 32 healthy subjects, nine CML patients, and nine LR patients were submitted to the optimized protocol. By measuring the light emission elicited by four concentrations of neutrophils, we were able to estimate the activity of LAP per cell (the slope of the curve obtained by linear regression). A high linear correlation was found between the chemiluminescent result (slope) and the cytochemical score. The slope for healthy individuals ranged between 0.61 and 8.49 (10(-5) mV.s/cell), with a median of 2.04 (10(-5) mV.s/cell). These results were statistically different from those of CML patients (range = 0.07-1.75, median = 0.79) and LR patients (range = 3.84-47.24, median 9.58; P < 0.05).
Keywords: chemiluminescence; leukocyte alkaline phosphatase; Immulite (R) (AMPPD); chronic myeloid leukemia; leukemoid reactions